A MUSA E HOMERO - Brandão, Jacyntho Lins (Organon, 2012)
It is a work about some ideas which appear both in poems of Homero and Hesíodo: the statueof the poet, the poem and its public, considering the features of the greek poem since its origins. Thoeseideas will have essential importance in posterior theories.